Experiences of Spanish out-of-hospital emergency workers with high levels of depression during the COVID-19 pandemic: a qualitative study - Susana Navalpotro-Pascual; María Paz Matellán-Hernández; Elena Pastor-Benito; Raúl Soto-Cámara; Rosa M Cárdaba-García; Noemi García-; Henar Onrubia-Baticón; Vinita Mahtani-Chugani (BMC, 2024)
Abstract Background The COVID-19 pandemic had a major psychological impact on health care workers (HCWs). This study was embedded in a larger quantitative study on the mental health care of out-of-hospital HCWs in Spain. To better understand this, a qualitative study was conducted to explore the experiences, coping strategies, and influencing factors of out-of-hospital HCWs who scored high (> 25 points) on the Depression Anxiety Stress Scale (DASS-21) in a previous quantitative mental health study. Methods A qualitative study was conducted using six in-depth interviews with individuals who scored high on the depression scale and agreed to be contacted by email between May and June 2021, using the phenomenological approach. The data were analysed using Brawn and Clare's method. Results The main results findings related to four themes. The emotional impact of assuming a professional role with high self-demands and responsibilities; Factors influencing the development of negative emotions such as the cruelty of the pandemic, the helplessness in relation to health management and policy, the changing role of the professional and the relationship with society; Personal protection through coping strategies to manage negative emotions such as support from colleagues and family; Good practices for the future looking for different management strategies that can influence individuals and their personal, professional, and social relationships. Conclusion The strong impact of the circumstances experienced points to the need to develop psychological support programmes that can protect people's mental health from depression during a crisis and improve the relationship between workers and their managers.